Distribution and Bioconcentration of Polycyclic Aromatic Hydrocarbons in Surface Water and Fishes - Li, Haiyan (The Scientific World Journal, 2012)
To examine spatial distribution and bioconcentration of PAHs, water and fish samples were collected from Pearl River Delta in summer and spring, respectively. Particulate organic carbon, dissolved organic carbon, biodegradable DOC (BDOC), and chlorophyll a were measured. PAHs were dominated by 2- and 3-ring compounds in the water and SPM samples. Aqueous and solid-phase PAHs, respectively, showed significant correlations with total organic matter (TOC) in SPM or dissolved organic matter (DOC) in the water. The in-situ partitioning coefficients (logK (oc), mL/g) for the samples were observed to be related to logK (ow), implying that the hydrophobicity of PAHs is a critical factor in their distribution. It was also observed that BCF increased with the increasing K (ow) in the viscera of tilapia (logBCF = 0.507logK (ow) − 1.368, r = 0.883). However, most of the observed log BCF values in other different fish tissues at first increased with the increasing of log K (ow), then reached a maximum value when logK (ow) is between 5 and 7, and then decreased when logK (ow) is higher than 7, indicating that the value of BCF may vary due to the diversity of fish species.